Fast Transfer of Triplet to Doublet Excitons from Organometallic Host to Organic Radical Semiconductors - Gu, Qinying (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.